2007
DOI: 10.1097/wad.0b013e318065c495
|View full text |Cite
|
Sign up to set email alerts
|

A 24-week Randomized, Controlled Trial of Memantine in Patients With Moderate-to-severe Alzheimer Disease

Abstract: This study examined the efficacy and safety of memantine monotherapy in patients with moderate-to-severe Alzheimer disease (AD). Patients not receiving a cholinesterase inhibitor (N=350) were randomized to receive memantine (20 mg/d) or placebo during this 24-week, double-blind, placebo-controlled trial. Prospectively defined analyses failed to demonstrate a statistically significant benefit of memantine treatment compared with placebo on the Severe Impairment Battery (SIB) at week 24 end point, although a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 16 publications
2
136
2
2
Order By: Relevance
“…Nine relevant studies had accessible data and were included in the post hoc responder analyses (table 1). These included the 6 pivotal phase III memantine studies previously evaluated by the EMA [3,7,8] (MEM-MD-10 [11], LU-99679 [12], MEM-MD-12 [13], MRZ-9605 [14], MEM-MD-01 [15], and MEM-MD-02 [16]) as well as 3 additional studies which have become accessible since then (IE-2101 [17], LU-10116 [18], and MEM-MD-22 [19]). All studies were 24 weeks in duration, except for study MRZ-9605 (28 weeks) and study LU-10116 (16 weeks).…”
Section: Methodsmentioning
confidence: 99%
“…Nine relevant studies had accessible data and were included in the post hoc responder analyses (table 1). These included the 6 pivotal phase III memantine studies previously evaluated by the EMA [3,7,8] (MEM-MD-10 [11], LU-99679 [12], MEM-MD-12 [13], MRZ-9605 [14], MEM-MD-01 [15], and MEM-MD-02 [16]) as well as 3 additional studies which have become accessible since then (IE-2101 [17], LU-10116 [18], and MEM-MD-22 [19]). All studies were 24 weeks in duration, except for study MRZ-9605 (28 weeks) and study LU-10116 (16 weeks).…”
Section: Methodsmentioning
confidence: 99%
“…[214][215][216] It has also been shown to improve behavioural disturbances, such as agitation and aggression. Its mechanism of action as an NMDA receptor antagonist differs from the cholinesterase inhibitors approved for the treatment of Alzheimer disease (i.e., donepezil, galantamine and revastigmine), suggesting a theoretical potential to be used in combination with these drugs.…”
Section: Glutamate Antagonists In the Treatment Of Alzheimer Diseasementioning
confidence: 99%
“…The magnitude of benefit from treatment with memantine is similar to the magnitude observed for AChE-Is. Two of three moderate to severe AD trials with memantine showed statistical significance on their primary outcomes (Reisberg et al 2003b;van Dyck et al 2007), including an add-on trial, in which patients on long-term treatment with donepezil, randomized to receive either placebo or add-on memantine, showed that add-on therapy with memantine produced a statistically significant benefit compared to add-on therapy with placebo (Tariot et al 2004).…”
Section: Memantinementioning
confidence: 99%